Fiction in nonfiction the difference between fabrication and fabulation - Laqui, Patrick Justin J. (College of Arts and Letters, University of the Philippines Diliman, 2005)
My thesis aims to justify the presence of non-factual elements in creative nonfiction. Critics of this relatively new genre find all sorts of problems with creative nonfiction's paradoxical nature - the use of fiction (techniques in fiction) to tell a true story (an oxymoron itself). By acknowledging how facts, memory, and perspective can be problematic in terms of their reliability, the presence of "lies" in a work of nonfiction is justified because no one can really write a true story because the basis of truth, the reality we perceive, is something we cannot fully grasp and write about. What creative nonfiction writers do employ, to give their writing "teeth", is the Actual. This refers to simple actuality, void of the assumptions that the words Fact, Real, and Truth carry. But this doesn't mean that the writer is free to write fiction and pass it off as nonfiction. Even if distorting the truth is made permissible in creative nonfiction, for specific reasons that this thesis will reveal, a distinction between fiction and nonfiction has to be made. There is a difference between a story and a true story. Through a discussion of the extreme form of fabrication, as seen in the work of Stephen Glass, the limits of truth distortion will be defined. Two rules taken from Roy Peter Clark's essay, "The Line Between Fact and Fiction", will be used to distinguish between fabrication (fiction) and fabulation (creative nonfiction).